Subacute Sclerosing Panencephalitis (SSPE): A Rare Case Report - Islam, Mohammad Rafiqul; Bhuiyan, Mamunur Rashid; Deb, Sudip Ranjan; Kabir, Ahmedul (Journal of Medicine, 2015)
Subacutesclerosingpanencephalitis(SSPE) is a late complication of measles virus infection. It presents with psychiatric manifestation, progressive dementia, myoclonic jerk and other focal neurological signs. The diagnosis is based upon characteristics clinical manifestation, the presence of characteristic periodic EEG discharge, and demonstration of raised antibody titer against measles in plasma and cerebrospinal fluid. In our case patient presented with behavioral change, myoclonic jerk, characteristic EEG and elevated level of antibody both in serum and CSF. DOI: http://dx.doi.org/10.3329/jom.v16i1.22403 J MEDICINE 2015; 16 : 51-52